GAMBARAN STATUS GIZI PADA SISWA SEKOLAH DASAR DI DESA TELUK KIAMBANG KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR. - Siregar, Yesti Hana Wiliya; Ernalia, Yanti; Restuastuti, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTNutritional status is the health status generated by the balance of the needs and input of nutrients or nutrients. Primary school children is one of the group that is susceptible to nutritional problem, underweight and overweight. The purpose of this study was to describe the nutritional status in children of primary school in Teluk Kiambang at Tempuling, Indragiri Hilir. This research is a descriptivestudy with cross-sectional design. Respondents in this research were student in grade 1-6 which consists of 400 people chosen by total sampling method. Data were collected by questionnaire filled out by the parents of the respondents to determine student characteristic data and calculate BMI by measuring height and weight to measure the nutritional status of students. Nutritional status is divided into malnutrition, underweight, normal, overweight and obese based on anthropometric standard with BMI/U indicator. The data showed that underweight nutritional status as the highest value were 153 people (38,3%), followed by normal nutritional status were 145 orang (36,3%), malnutrition nutritional status were 94 people (23,5%), overweight nutritional status were 7 people (1,8%) and obesity nutritional status were 1 people (0,3%). The conclusion of this studyis the average of the nutritional status of children has malnutrition nutritional the age group 6-9 years, male gender, education level of parents is elementary, the amount of revenue < UMR and a majority of the number of children > 2.Keywords: children of school age, nutrition, nutritional status